Mineração e Desenvolvimento Educacional: Estudo Sobre a Formação Profissional Qualificada Através da Parceria Senai-Mineradora no Município de Juruti - Pá - SILVA, Raissa Farias da (Universidade Federal do Oeste do Pará, 2024)
The mining industry is an essencial economic activitys to human development. Ever since prehistory, the frist humans have been made use of mining resources and, after that, the ores and minerals it was adopted more and more in the day by day of human civilization. Today, the mining became extremilly necessary to surviving and it is not possible to get a any technologicol, social or human development without its. In favour of the necessity of mineral use, more and more the mining grow up e, thereby, it needs for workers. However, in many locations where the mining explores the minerals there are not enough skilled labour to meet this demands. Thus, it is necessary that the mining company invests in education of that county where operates for improve the workforce and to get them. Cases like this are very common, although, in a few ocasions heve not the due divulgation or treatment about it. In Juruti-PA, a large exemple of this is the colaboration made between the mining company Alcoa and the educational institution SENAI, wich through professional qualification heve been gradueted several professionals to operete in the local Market. Given this fact, an attempt was made to study about the improvement wich the mining has been made in the educational development of Juruti county, reflecting in the number of people reached and benefited for that relationship. For this, was done the application of a questionnaire to the local people in order to achieve the most involvement as possible of the egressed students, besides to do use of bibliographic and documentery research to get the number of the vacancies and courses offering since of the opening the educational institution. The got it results through the reseach show up the biggest contribution wich that relationship created to the county and the people of Juruti about the educational development and the qualified professional training. Moreover, it was possible to know the profile and employment situation of the egressed students. Therefore, it is considered that this investigation was very revelent to the society and academic community who will be able to take benefits with this informations gathered through this reseach.